2016
DOI: 10.1515/scjme-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis of an Evaporative Cooling System

Abstract: The use of chlorofluorocarbon based refrigerants in the air-conditioning system increases the global warming and causes the climate change. The climate change is expected to present a number of challenges for the built environment and an evaporative cooling system is one of the simplest and environmentally friendly cooling system. The evaporative cooling system is most widely used in summer and in rural and urban areas of India for human comfort. In evaporative cooling system, the addition of water into air re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…M. H. SHAIK et al (2020) performed a first and second law analysis of low GWP refrigerants as a stand-in to refrigerator and from that they conclude that HFO-1234yf is the elite option for swap to R134a in a refrigerator without changes [14]. Kapilan et.al conducted a computational fluid dynamic analysis to study the refrigerator and air-conditioning evaporative cooling system [15]. SK Mohammad Hasheer and Kolla Srinivas (2019) performed theoretical analysis of different refrigerant mixtures as stand-in to R-134 in refrigerator and from that analysis they concluded that R152A/ HFO-1234ze (E) (by mass 50:50) can be utilized as an immediate trade for HFC-134a without rolling out any improvements to the compressor [16].…”
Section: Introductionmentioning
confidence: 99%
“…M. H. SHAIK et al (2020) performed a first and second law analysis of low GWP refrigerants as a stand-in to refrigerator and from that they conclude that HFO-1234yf is the elite option for swap to R134a in a refrigerator without changes [14]. Kapilan et.al conducted a computational fluid dynamic analysis to study the refrigerator and air-conditioning evaporative cooling system [15]. SK Mohammad Hasheer and Kolla Srinivas (2019) performed theoretical analysis of different refrigerant mixtures as stand-in to R-134 in refrigerator and from that analysis they concluded that R152A/ HFO-1234ze (E) (by mass 50:50) can be utilized as an immediate trade for HFC-134a without rolling out any improvements to the compressor [16].…”
Section: Introductionmentioning
confidence: 99%
“…Heat recovery represents a basic tool for reducing energy consumption in heating, ventilation and air conditioning (HVAC) systems. The most important part of each heat recovery system is the heat exchanger [1,18]. Oscillating (or pulsating) heat pipes -OHPoriginally presented by Akachi provide new possibilities for heat transfer devices thanks to their unique two-phase heat transfer mechanism [2].…”
Section: Introductionmentioning
confidence: 99%
“…From those experiments, they came to conclusion that HFO-1234yf and R152a have a very good substitute to HFC-134a.Hasheer and Srinivas [13] conducted a theoretical investigation on low GWP refrigerants as a direct substitute to R134a in a domestic refrigerator and conclude that R1234yf can be used as a direct substitute to R134a. Kapilan et.al [14] performed a CFD analysis is used to analyse the evaporative cooling system in a refrigerator and air-conditioning system. KABÁT Juraj et.al [15] performed an experiment on heating, ventilation and air conditioning systems and conclude that the onset of stable oscillations of the working fluid heavily increases the heat transfer performance compared to the empty heat exchanger.so heat exchanger also plays an important role in improving the performance of a refrigeration system.…”
Section: Introductionmentioning
confidence: 99%